The Legal Protection for Buyers of Plots of Land with the Power to Sell in Demak Regency - Dyawati, Elisya Triwi (TABELLIUS: Journal of Law, 2024)
The public's interest in buying and selling land continues to grow because land is an economic factor that plays an important role and has strategic value. The basis of buying and selling land is that there is an agreement between the seller and the buyer, because the limited land population is not commensurate with the increasing population, business people find a new way of doing business by breaking up a plot of land called a plot of land and buying and selling it with a letter. power of attorney granted by the power of attorney as the owner of a plot of land. The aim of this research is to find out how the process of buying and selling plots of land using a power of attorney in Demak is and to find out the weaknesses of buying and selling plots of land using a power of attorney in Demak. This research method cannot be separated from the aim of directing problem solving using an empirical juridical approach method. The research approach is used to look at events or happenings in a society using descriptive research specifications so that in this research it describes, describes or describes an incident of buyer protection through a power of attorney to sell in land buying and selling of plots of land, using data in the form of interview results. along with the application of legal provisions relating to buying and selling using a power of attorney to sell, namely in the Civil Code and Government Regulation Number 24 of 1997 concerning Land Registration. The results of the research obtained are how the buyer's protection through a power of attorney to sell in land sale and purchase transactions always includes the PPAT in accordance with Article 1 point 24 of PP No. 24 of 1997, apart from making deeds related to land, then it can be used as a consultation with the buyer regarding the validity of the status. land along with a power of attorney to sell. The power of attorney to sell can then be examined first regarding the substance in the form of clauses stipulated by the power of attorney and then in a notarial deed at the notary, because the weakness of the power of attorney is seen in the substance of the power of attorney itself so that it can give rise to a dispute over land.